Predicting potential distributions of Monochamus saltuarius, a novel insect vector of pine wilt disease in China - Gao, Ruihe; Liu, Lei; Li, Rongjiao; Fan, Shiming; Dong, Jianghai; Zhao, Lijuan (Frontiers in Forests and Global Change, 2023)
Monochamus saltuarius Gebler was first identified as a new vector of pine wilt disease in Northeast China in 2018, and monitoring of M. saltuarius has become a key strategy to prevent and control the disease in this region. However, the potential distributions of M. saltuarius in China are unclear. In this study, we clarified bioclimatic environmental variables affecting the distribution of M. saltuarius, predicted the geographically suitable habitats of M. saltuarius in current and future climate conditions, and determined changes in the spatial pattern of a suitable distribution area of M. saltuarius under current and future climate conditions. This is the first study to use the optimized maximum entropy model and ArcGIS to accurately predict suitable geographical areas for M. saltuarius based on different climatic conditions in China. and the average area under the receiver operating characteristic curve reached 0.954 ± 0.0024. Of the 32 bioclimatic variables, temperature seasonality, precipitation of wettest month, precipitation seasonality, maximum temperature of the warmest month, and elevation played significant roles in determining the potential distribution of M. saltuarius, with contribution rates to the model of 32.1, 31.8, 11.5, 7.5, and 6.5%, respectively. Under the current climate scenario, the predicted suitable areas for M. saltuarius were mainly at latitudes north of 33° in China, and larger suitable areas were mainly distributed in Northeast China and North China, with areas of 87.04 × 104 and 73.15 × 104 km2, respectively. Using future climatic scenarios SSP126 and SSP585, the predicted suitable areas of M. saltuarius will continue to expand from that of 2040, 2070, and 2100, with highly and moderately suitable areas showing larger increasing trends but low suitable distribution areas will decrease to varying degrees. The potential suitable areas of M. saltuarius may increase greatly in Northwest, Central, and Eastern China. This study provides important scientific theoretical knowledge for effectively controlling and preventing M. saltuarius and pine wilt disease in northern China.